Apropriações de conhecimentos em uma formação continuada colaborativa com foco na produção e reescrita de textos nos anos iniciais - Pardinho, Jocieli Aparecida de Oliveira (2021)
On this research, we approach the Collaborative Continuing Formation theme (also known as CCF) in their relation to the text‟s production and rewriting on beginning years. From this thematic, the general aim contemplates the following search question: what knowledge ownerships are possible to identify, in CCF participants, about the forwarding of textual‟s production and rewriting, subsidized by the conception of writing as an integration activity? As a theoretical contribution, we are guided on an interactionist-dialogical perspective of language, according to the writings of Bakhtin‟s Circle (VOLÓCHINOV and BAKHTIN, 1926; VOLÓCHINOV, 2018 [1929]; BAKHTIN, 2011 [1979], among others), in which we understand the writing‟s practice as a labor, process (GERALDI, 1997; MENEGASSI, 2010, 2016) and an interactive activity (BAKHTIN, 2011 [1979], COSTA-HÜBES, 2012). We resort to Historical-Cultural field (VYGOTSKY, 1991 [1984]), SMOLKA, 2000) to explain the process of knowledge‟s “ownership” and, related to CCF, we started by Vygotsky‟s (1991 [1984]) and Magalhães‟ (2004) precepts. Thus, as of a diagnostic survey (questionnaire and interview), we developed a CCF process with primary school teachers from the city of Ubiratã-PR, focused on texts‟ production and rewriting. The data were generated throughout the whole formative process (conceptual maps and elaboration of activities). Methodologically, it is a research which is inserted in the Applied Linguistics area (MOITA LOPES, 2003), as a qualitative-interpretative stamp, educational ethnographic (JUNG; SILVA; SANTOS, 2019) and critic collaborative search-action (MAGALHÃES, 2004; PIMENTA, 2005). The search results highlight to knowledge ownerships reverberated by the participant docents related to the beginning years textual production and rewriting practice referral, like: a) the comprehension of the different language and writing conceptions and their influences on PL learning; b) the knowledge about the writing practice as in interactive activity and its relevance on the work with the textual production shaft; c) the elaboration of production‟s referral contemplating interaction elements; d) the recognition of the text‟s revision/correction practice in the promotion of writing practice subsidized by the interactionist-dialogical language‟s conception. Soon, we highlight that a CCF process can boost, by theoretical-methodological confrontations, the (re)construction of the docent know related to their praxis in the classroom, which can justify the need of higher investment in CCF.